Chapter Salerno: il porto e le metamorfosi del waterfront - Russo, Maria (Proceedings e report, 2020)
The port of Salerno, one of the largest on the Tyrrhenian coast, was implanted in the Middle Ages west of the city. Deteriorated over time due to neglect and serious problems of cover-up afflicting the area, it was replanted after the unification of Italy, creating a closed basin with the mouth turned to the east. The wrong orientation and the massive landfill phenomena supervening, led to the severe erosion of the eastern beach, on which it stood the city. In order to cope with the phenomena, in the last decades of the nineteenth and early twentieth centuries, multiple defense interventions were carried out by sheltered cliffs that filled the coast with the total metamorphosis of the coastal strip.